Cenas sob a interdição: o cinema pós-condenação de Jafar Panahi - Reis, Breno Almeida Brito (2020)
This research analyses Iranian filmmaker Jafar Panahi's filmmaking processes following the court ruling that has banned him for twenty years from making films, writing screenplays, giving interviews and leaving Iran. Nevertheless, Panahi continues filming discreetly, independently and clandestinely, having thus made This is not a film (2011), Closed Curtain (2013), Taxi (2015), Where are you, Jafar Panahi? (2016) and 3 Faces (2018). I address what is outlined in these films as a filmic thinking of interdiction. In identifying the aesthetic marks and filmmaking strategies that Panahi came to explore, I describe the main lines of his postcondemnation filmic project, analysing how these films confront, negotiate, and transgress the restrictive conditions of interdiction. Keywords: Iranian cinema. Censorship. Self-inscription. Confinement.